Androgen Elevation Accelerates Reproductive Senescence in Three-Spined Stickleback - Simons, Mirre J. P.; Sebire, Marion; Verhulst, Simon; Groothuis, Ton G. G. (Frontiers in Cell and Developmental Biology, 2021)
Costs of reproduction shape the life-history evolution of investment in current and future reproduction and thereby ageing. Androgens have been proposed to regulate the physiology governing these investments. Furthermore, androgens are hypothesized to play a central role in carotenoid-dependent sexual signalling, regulating how much carotenoids are diverted to ornamentation and away from somatic maintenance, increasing oxidative stress and accelerating ageing. We investigated these relationships in male three-spined stickleback in which we elevated 11-ketotestosterone, and supplied vitamin E, an antioxidant, in a 2x2 design. Androgen elevation shortened the time stickleback maintained reproductive activities. We suspect that this effect is caused by 11-ketotestosterone stimulating investment in current reproduction, but we detected no evidence for this in our measurements of reproductive effort: nest building, body composition and breeding colouration. Carotenoid-dependent colouration was even slightly decreased by 11-ketotestosterone elevation and was left unaffected by vitamin E. Red colouration correlated with life expectancy and reproductive capacity in a quadratic manner, suggesting overinvestment of the individuals exhibiting the reddest bellies. In contrast, blue iris colour showed a negative relationship with survival, suggesting physiological costs of producing this aspect of nuptial colouration. In conclusion, our results support the hypothesis that androgens regulate investment in current versus future reproduction, yet the precise mechanisms remain elusive. The quadratic relationships between sexual signal expression and aspects of quality have wider consequences for how we view sexual selection on ornamentation and its relationship with ageing.